A week in the life of Corinth - Witherington, Ben, 1951- (Downers Grove, IL : IVP Academic, 2012)
Intrigue is in the air as Nicanor returns to Corinth and reports to his patron Erastos on recent business dealings in Rome. Nicanor, a former slave, is a man on the make. But surprises keep springing up in his path. A political rival of Erastos is laying a plot, and a new religion from the East keeps pressing in his life. Spend an imaginary week in Paul's Corinth as the story of Nicanor winds through street and forum, marketplace and baths, taking usChristian world.Numerous full-page text boxes expand on a variety of aspects of life and culture as we encounter them in the narrative. into shop, villa and apartment, where we meet friends new and old. From our observing a dinner in the temple of Aesclepius to Christian worship in the home of Erastos, Paul's dealings with the Corinthians in his letters take focused relevance and socail clarity. The result is an unforgettable introduction to life in a major center of the New Testament world. Throughout the text, helpful sidebars, maps and diagrams serve to further illuminate the sociocultural context of the early Christian world.
Poseidon's revenge -- Isthmia and its games -- Paulos, Priscilla, and Aquila -- The home of Erastos -- The enmity of the enemy -- Gallio's gall -- Erastos goes missing -- The proposition -- The trial of Paulos -- Julia's prayers and Nicanor's protection -- The Subura and the Sabbath -- Paulos, Priscilla, and Erastos -- "Dies Solis": the morning of the day of the sun/Son -- The afternoon of the day of the sun -- The end of the day.
Keywords: Paul, -- the Apostle, Saint -- Fiction; Bible. -- History of Biblical events -- Fiction; Christian saints -- Fiction; Apostles -- Fiction; Corinth (Greece) -- Fiction; Biographical fiction; Christian fiction